2022
DOI: 10.1001/jamanetworkopen.2022.14460
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nighttime Masked Uncontrolled Hypertension With Left Ventricular Hypertrophy and Kidney Function Among Patients with Chronic Kidney Disease Not Receiving Dialysis

Abstract: IMPORTANCE Nighttime hypertension is prevalent and associated with adverse outcomes in patients with chronic kidney disease (CKD), but nighttime hypertension, a subtype of masked uncontrolled hypertension (MUCH), is often undetected among patients with controlled office blood pressure. Little attention has been paid to patients with CKD and nighttime MUCH. OBJECTIVETo investigate the prevalence of nighttime MUCH and its associations with cardiovascular and kidney outcomes in patients with CKD who were not rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Recently, Janus et al ( 50 ) reported that a panel of brain natriuretic peptides, FGF-23, fibrinogen, and high-sensitive troponin T can be used to predict heart failure in patients with CKD. In addition, Fu et al ( 51 ) found that nocturnal hypertension is associated with LVH in patients with CKD, indicating that ambulatory blood pressure monitoring may be used as an important indicator to evaluate the risk of uremic cardiomyopathy. Further studies are required to confirm these.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Janus et al ( 50 ) reported that a panel of brain natriuretic peptides, FGF-23, fibrinogen, and high-sensitive troponin T can be used to predict heart failure in patients with CKD. In addition, Fu et al ( 51 ) found that nocturnal hypertension is associated with LVH in patients with CKD, indicating that ambulatory blood pressure monitoring may be used as an important indicator to evaluate the risk of uremic cardiomyopathy. Further studies are required to confirm these.…”
Section: Discussionmentioning
confidence: 99%
“…Nighttime hypertension and non-dipping circadian blood pressure pattern are risk factors for cardiovascular complications [ 31 ]. Nighttime hypertension (more precisely: masked uncontrolled nighttime hypertension) was a risk factor for left ventricular hypertrophy in adult Chinese patients with CKD [ 32 ]. In the analysis of patients from the 4C study, elevated night-time blood pressure was associated with increased markers of arterial damage and with left ventricular hypertrophy, and isolated nighttime hypertension was associated with thickening of common carotid artery intima-media thickness [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension, a chronic condition of elevation in blood pressure (BP), is a well-known risk factor for the development of cardiovascular diseases (CVDs), including heart failure, coronary heart diseases, myocardial fibrosis, and infarction [ 1 ], atherosclerosis [ 1 , 2 ], stroke [ 1 , 3 ], and kidney failure [ 4 ]. The pathogenesis of hypertension is multifaceted, and one of the well-characterized causes is endothelial dysfunction resulting from nitric oxide (NO) deficiency [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%